Dual Anion–Cation Reversible Insertion in a Bipyridinium–Diamide Triad as the Negative Electrode for Aqueous Batteries. Issue 8 (27th December 2017) - Perticarari, Sofia; Sayed‐Ahmad‐Baraza, Yuman; Ewels, Chris; Moreau, Philippe; Guyomard, Dominique; Poizot, Philippe; Odobel, Fabrice; Gaubicher, Joël
Abstract: Aqueous batteries are an emerging candidate for low‐cost and environmentally friendly grid storage systems. Designing such batteries from inexpensive, abundant, recyclable, and nontoxic organic active materials provides a logical step toward improving both the environmental and economic impact of these systems. Herein the first ever battery material that works with simultaneous uptake and release of both cations and anions is proposed by coupling p‐type (bipyridinium) and n‐type (naphthalene diimide) redox moieties. It represents one of a new family of electrode materials which demonstrates an optimal oxidation potential (−0.47 V vs saturated calomel electrode), extremely fast kinetics, a highly competitive capacity (63 mA h g −1 at 4 C ), and cyclability in both neutral Na + and Mg 2+ electrolytes of molar range concentration. Through a combination of UV–vis spectroelectrochemistry, electrochemical quartz‐crystal microbalance, Operando synchrotron‐X‐ray diffraction, and density functional theory calculations a novel dual cation/anion insertion mechanism was proven and rationalized. Based on these findings, this innovative p/n‐type product may well provide a viable option for use as a negative electrode material, thereby promoting the design of cutting‐edge, low‐cost, rocking‐chair dual‐ion aqueous batteries. Abstract : The first ever battery material that works with simultaneous uptake and release of both cations and anions is proposed for low cost aqueous batteries. The two redox subunits p‐type‐bipyridinium and n‐type‐naphthalene‐diimide synergistically cooperate during the electrochemical process, leading to highly competitive performance in both neutral Na + and Mg 2+ electrolytes. The novel insertion mechanism is rationalized by UV‐spectroelectrochemistry, electrochemical quartz‐crystal microbalance, Operando‐synchrotron‐X‐ray diffraction, and density functional theory calculations.